Implementation of screening and management of household contacts of tuberculosis cases in Daru, Papua New Guinea - Honjepari, A. (Public Health Action, 2019)
SETTING: Daru Island, Western Province, Papua New Guinea (PNG). OBJECTIVE: To describe the implementation of a screening programme for household contacts of tuberculosis (TB) cases residing on Daru Island. DESIGN: This was a retrospective descriptive study evaluating two periods of implementation: introduction and expansion of a screening programme for household contacts of drug-resistant TB (DR-TB) cases (March 2016 to September 2017), and inclusion of drug-susceptible TB (DS-TB) cases with provision of preventive therapy for eligible contacts between October 2017 and March 2018. RESULTS: In the first period, the contact screening programme was established and strengthened by increasing coverage over time. There was a large number of contacts (median 8) in each household, and a high uptake of screening. In the second period of evaluation, respectively 412 and 223 contacts of 42 DS-TB and 25 DR-TB index cases were screened. Overall, 156 (24.6%) contacts reported TB-related symptoms and 9 (1.4%) were diagnosed with active TB. All 9 commenced TB treatment: 5 had DS-TB and 4 had DR-TB. Of 82 child contacts of DS-TB cases eligible for preventive therapy, 57 (69.5%) commenced treatment and 45 completed treatment. CONCLUSION: Community-based household contact screening and management was successfully implemented under programme conditions in this high burden TB and DR-TB setting in PNG.